The Role of Navigated Transcranial Magnetic Stimulation Motor Mapping in Adjuvant Radiotherapy Planning in Patients With Supratentorial Brain Metastases - Schwendner, Maximilian J.; Sollmann, Nico; Diehl, Christian D.; Oechsner, Markus; Meyer, Bernhard; Krieg, Sandro M.; Combs, Stephanie E. (Frontiers in Oncology, 2018)
Purpose: In radiotherapy (RT) of brain tumors, the primary motor cortex is not regularly considered in target volume delineation, although decline in motor function is possible due to radiation. Non-invasive identification of motor-eloquent brain areas is currently mostly restricted to functional magnetic resonance imaging (fMRI), which has shown to lack precision for this purpose. Navigated transcranial magnetic stimulation (nTMS) is a novel tool to identify motor-eloquent brain areas. This study aims to integrate nTMS motor maps in RT planning and evaluates the influence on dosage modulations in patients harboring brain metastases. Materials and Methods: Preoperative nTMS motor maps of 30 patients diagnosed with motor-eloquent brain metastases were fused with conventional planning imaging and transferred to the RT planning software. RT plans of eleven patients were optimized by contouring nTMS motor maps as organs at risk (OARs). Dose modulation analyses were performed using dose-volume histogram (DVH) parameters. Results: By constraining the dose applied to the nTMS motor maps outside the planning target volume (PTV) to 15 Gy, the mean dose (Dmean) to the nTMS motor maps was significantly reduced by 18.1% from 23.0 Gy (16.9 – 30.4 Gy) to 18.9 Gy (13.5 – 28.8 Gy, p<0.05). The Dmean of the PTV increased by 0.6 ± 0.3 Gy (1.7%, p<0.05). Conclusion: Implementing nTMS motor maps in standard RT planning is feasible in patients suffering from intracranial metastases. A significant reduction of the dose applied to the nTMS motor maps can be achieved without impairing treatment doses to the PTV. Thus, nTMS might provide a valuable tool for safer application of RT in patients harboring motor-eloquent brain metastases.